Ekualisasi Pengakuan Pendapatan antara SPT Masa PPN dan Laporan Keuangan Bulanan terhadap Kepatuhan Perpajakan - Rahmatulloh, Hanif Dzaky; Yudhanti, Ashari Lintang (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Tax compliance in Indonesia remains a critical issue under the self-assessment system, where taxpayers are responsible for calculating, reporting, and paying their taxes. One recurring problem is the potential inconsistency between monthly Value Added Tax (VAT) returns and company financial statements, which may trigger administrative risks and reduce transparency. This study aims to examine the equalization of revenue recognition between monthly VAT returns and financial statements of CV XYZ, a retail company engaged in mobile phone sales and accessories, and to evaluate its implications for tax compliance. The research employed a descriptive qualitative approach, using primary data from interviews and observations during an internship at a public accounting firm, and secondary data from company records and relevant literature. The findings reveal that the total revenue recorded in the 2024 financial statements, amounting to IDR 20,806,984,947, was consistent with the total reported in monthly VAT returns, with no discrepancies identified. This result demonstrates that CV XYZ has applied accurate accounting practices, maintained compliance with tax regulations, and implemented effective internal controls. The study highlights that equalization not only minimizes the risk of penalties but also enhances transparency, credibility, and reliability in financial and tax reporting, offering practical insights for retail businesses with high transaction volumes.